Analysis of the Effect of Hard Skills, Soft Skills and Self Efficacy on the Quality of Human Resources in Universities in Region 3 Cirebon - Maulana, Muhammad Bayu; Dewi, Silvi Rahmawati; Maryam, Siti (Rescollacom (Research Collaborations Community), 2024)
This study aims to analyze the influence of Hard Skills, Soft Skills, and Self-Efficacy on the quality of human resources (HR) in higher education in region III Cirebon, West Java, Indonesia. This study used 283 samples from 3 universities in region 3 Cirebon. the research methodology uses quantitative, using multiple linear regression analysis to test the relationship between independent variables (Hard Skills, Soft Skills, and Self-Efficacy) with the dependent variable (HR quality). The findings from the research indicate that: 1. Hard skills have a significant positive impact on HR Quality, as evidenced by a t-count of 3.996, which exceeds the t-table value of 1.968. 2. Similarly, Soft skills also exert a significant positive influence on HR Quality, as shown by a t-count of 3.420, surpassing the t-table value of 1.968. 3. The influence of Self Efficacy on HR Quality is also positive and significant, as indicated by a t-count of 6.132, which is greater than the t-table value of 1.968. 4. Furthermore, the combination of Hard skills, Soft skills, and Self Efficacy collectively has a substantial positive effect on HR Quality, as demonstrated by an F-count of 151.383, which is higher than the F-table value of 2.64. These observations were made in the context of universities located in the Cirebon region. The implications of this study are significant for higher education institutions in Cirebon region III, as well as for broader education and human resource management practices. The findings underscore the importance of developing both Hard Skills and Soft Skills among university students, in addition to developing a positive self-efficacy mindset. This comprehensive approach to human resource development can lead to improved human capital quality, which is critical for economic and social development in the region.